ҚАРАҚАЛПАҚ ТИЛИН ЕЛЕ ДЕ ТЕРЕҢИРЕК ИЗЕРТЛЕЎ ҲӘМ РАЎАЖЛАНДЫРЫЎ ҲАҚҚЫНДА - Кощанов, К.М. (ILIM hám JÁMIYET, 2018)
The author of the article suggests objective and perfectly reliable ways for the solution of some issues in the development of the Karakalpak language that havent been decided yet.